2015
DOI: 10.1086/682276
|View full text |Cite
|
Sign up to set email alerts
|

Generational Spreading Speed and the Dynamics of Population Range Expansion

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Online enhancement: appendix.abstract: Some of the most fundamental quantities in population ecology describe the growth and spread of populations. Population dynamics are oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…22201/ib.20078706e.2021.92.3533 These results, as well as other biological traits such as continuous reproduction, a high proportion of female individuals (Ramírez-García et al, 2017), parental care associated with viviparity (Gross & Shine, 1981), and high tolerance to environmental degradation (Mercado-Silva et al, 2002) are consistent with successful invasive species (Sakai et al, 2001), since this success is related to their establishment, spread, and abundance (Hayes & Barry, 2008;Marchetti et al, 2004;Ricciardi, 2013;Ricciardi et al, 2013). Moreover, in the present study we found ontogenetic trophic overlap of P. bimaculatus and, considering the iteroparous reproductive biology of the species in the site (Ramírez-García et al, 2017), a clear generational overlap over time, facilitating the potential for spread and colonization and giving rise to the apparently rapid and successful establishment of P. bimaculatus in the Teuchitlán River (Bateman et al, 2015;Herrerías-Diego et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…22201/ib.20078706e.2021.92.3533 These results, as well as other biological traits such as continuous reproduction, a high proportion of female individuals (Ramírez-García et al, 2017), parental care associated with viviparity (Gross & Shine, 1981), and high tolerance to environmental degradation (Mercado-Silva et al, 2002) are consistent with successful invasive species (Sakai et al, 2001), since this success is related to their establishment, spread, and abundance (Hayes & Barry, 2008;Marchetti et al, 2004;Ricciardi, 2013;Ricciardi et al, 2013). Moreover, in the present study we found ontogenetic trophic overlap of P. bimaculatus and, considering the iteroparous reproductive biology of the species in the site (Ramírez-García et al, 2017), a clear generational overlap over time, facilitating the potential for spread and colonization and giving rise to the apparently rapid and successful establishment of P. bimaculatus in the Teuchitlán River (Bateman et al, 2015;Herrerías-Diego et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…) and calculating more accurate spread speeds for stage‐structured invasives (Bateman et al . ). An interesting way to incorporate climate change would be to develop the IDE analogue of the RDE found in Li et al .…”
Section: Extending Mhms: Potential Applications To Global Change Biologymentioning
confidence: 97%
“…IDEs have a long history of use for invasive species. Recent developments include modelling competing genotypes of pest species (Kanary et al 2014) and calculating more accurate spread speeds for stage-structured invasives (Bateman et al 2015). An interesting way to incorporate climate change would be to develop the IDE analogue of the RDE found in Li et al (2014).…”
Section: Extending Mhms: Potential Applications To Global Change Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential issue in estimating parameters may arise if multiple combinations of two or more parameters produce the same ecological outcome. For example, two species with different life-history strategies can generate the same spread patterns (Bateman et al 2015). This issue of non-identifiability of parameters makes it statistically challenging to infer the life-history tactics of an invader, which, in turn, can limit our ability to determine which life-history parameters play an outsized role in the species spread and, therefore, should be the target of management efforts (Crouse et al 1987).…”
Section: Introductionmentioning
confidence: 99%